2017
DOI: 10.1080/10942912.2017.1368554
|View full text |Cite
|
Sign up to set email alerts
|

DNA protection activity of a hydroethanol extract and six polyphenol monomers fromMorus alba L. (mulberry) twig

Abstract: Morus alba L. (mulberry) is one of the most important medicine and food crops in China and other developing countries in Asia due to its large biomass (twigs) and useful by-products. Additionally, its twigs are an excellent green resource for bioactive compounds that are resistant to ultraviolet (UV) radiation and that can whiten skin and scavenge free radicals, and are of potential interest to the cosmetics and health food industries. In this study, we evaluated the ability of Morus alba L. twig hydroethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The root is considered a substantial site for the biosynthesis of mulberroside A via glycosylation of oxyresveratrol (hydroxy-resveratrol), which is found as a precursor in the root of M. alba [35]. Oxyresveratrol is known as one of the key compounds in M. alba twigs, following its monoor di-glucosylated moieties [36][37][38], which supports the non-statistically significant higher amount in the twigs than in the root barks in this study.…”
Section: Discussionsupporting
confidence: 85%
“…The root is considered a substantial site for the biosynthesis of mulberroside A via glycosylation of oxyresveratrol (hydroxy-resveratrol), which is found as a precursor in the root of M. alba [35]. Oxyresveratrol is known as one of the key compounds in M. alba twigs, following its monoor di-glucosylated moieties [36][37][38], which supports the non-statistically significant higher amount in the twigs than in the root barks in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Mulberroside A possesses pharmacological functions, such as antioxidant, anti-inflammatory, and anti-tyrosinase activities (Kim et al, 2010;Lu et al, 2017;Zhang & Shi, 2010). The results presented in the current study showed that mulberroside A reshaped gut dysbiosis, increased fecal and circulating SCFAs, reactivated colonic NLRP6 inflammasome signaling, and inhibited oxidative stress, resulting in its protection against IEB damage to reduce serum endotoxin (toxemia) in HFrD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…Our previous study showed that dietary HFrD‐driven gut dysbiosis, SCFAs metabolic disorder and NLRP6 inflammation signaling disruption caused IEB damage, which were possibly associated with the occurrence of hippocampal neuroinflammation (Li et al., 2019). Mulberroside A possesses pharmacological functions, such as antioxidant, anti‐inflammatory, and anti‐tyrosinase activities (Kim et al., 2010; Lu et al., 2017; Zhang & Shi, 2010). The results presented in the current study showed that mulberroside A reshaped gut dysbiosis, increased fecal and circulating SCFAs, reactivated colonic NLRP6 inflammasome signaling, and inhibited oxidative stress, resulting in its protection against IEB damage to reduce serum endotoxin (toxemia) in HFrD‐fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Mulberry branches, also known as Ramulus mori (RM), are included in the Chinese Pharmacopoeia as a herbal beverage, and mulberry branch extract (MBE) has been approved as a food source by the Chinese and Korean governments [3,4], indicating that MBE is safe for consumption. Mulberry branches are rich in active components such as flavonoids [5], alkaloids [1], and polysaccharides [6], which have various activities such as antioxidation [7] and hypoglycemic effects [8]. However, the chemical composition and biological activities of MBE of different varieties of mulberry trees vary greatly [7,9,10].…”
Section: Introductionmentioning
confidence: 99%